ANALISIS DAMPAK PENGGUNAAN REWARD DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA MUHAMMADIYAH ACEH SINGKIL - Saiful Akmal; Evi Susanti (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2019)
This study analyzes the impact of rewards in the learning process excercised in senior high schools in Aceh Singkil, especially in Islamic Education subject. Furthermore, this research tries to see what forms of reward are practiced in the learning process, what kinds of impacts arise from giving rewards in the learning process and finally, the supporting factors and obstacles in giving rewards in the selected school. The method used in this study is qualitative research. Data is collected from interviews and field notes. The results of this study indicate that the forms of giving rewards in the learning process of Islamic Education at Muhammadiyah High School in Gunung Meriah, Singkil include mainly introducing programs such as free snacks, pocket money, bags, shoes, uniforms, stationery, awards and trophies for students achievements, as well as giving motivation to students to a lesser extend. In addition, other findings also revealed both positive effects of rewards such as increasing student enthusiasm and achievement, as well as negative students, such as students tend to be more complacent and arrogant. With regard to supporting factors in giving rewards include strong encouragement and consistency of teachers and schools in motivating students. While a number of discouraging factors were also found, among others, the environment was not good, lack of awareness in students and lack of communication with parents of students.